Association between cumulative changes in the Wells score and the risk of stroke-associated pneumonia in patients with acute ischemic stroke: results from the REMISE study - Yu, Jing; Li, Dongze; Chen, Jin; Liu, Yi; Zhang, Wei; Zhong, Yan; Ma, Yan; Zeng, Zhi; Wu, Qinqin; Wan, Zhi (Frontiers in Neurology, 2026)
IntroductionThe Wells score, a reliable indicator of thrombotic burden, has been associated with stroke-associated pneumonia (SAP) in patients with acute ischemic stroke (AIS). However, the impact of changes in dynamic Wells scores on the incidence and severity of SAP remains poorly understood.MethodsA total of 767 participants with AIS were recruited from the Retrospective Multicenter Study for Ischemic Stroke Evaluation. Two Wells score measurements (i.e., at baseline and within the first 3 days) were obtained. Changes in dynamic Wells scores were then estimated using two indices: the cumulative Wells score and dynamic Wells score classes based on K-means analysis. The cumulative Wells score was calculated as the weighted sum of the mean Wells score value for each time interval (value × time). Dynamic Wells score classification was determined using K-means clustering analysis. Logistic regression was employed to analyze the effects of changes in dynamic Wells scores on the incidence of SAP.ResultsAmong the included patients, 263 developed SAP. Four dynamic Wells score classes were identified. The incidence of SAP increased significantly with increasing cumulative Wells scores. After adjusting for confounders, an elevated cumulative Wells score was significantly associated with an increased incidence of SAP (p < 0.001). Compared with the class 1 group, the class 2, 3, and 4 groups had odds ratios for SAP incidence of 2.01 (p = 0.048), 3.71 (p = 0.001), and 9.90 (p < 0.001), respectively. Adding changes in dynamic Wells scores to a conventional risk model for SAP improved discrimination and calibration. Changes in dynamic Wells scores were positively correlated with the pneumonia severity index.DiscussionChanges in dynamic Wells scores were independently associated with the incidence of SAP. Therefore, dynamic monitoring of changes in the Wells score may assist in the early identification of patients at high risk of developing SAP.